Comparison between the effect of GnRH agonist and HCG injection on the luteal phase support in patient undergoing IUI - Mohammed, Zahraa Ali; Selman, Mohammad Oda; Jawad, Mufeeda Ali; Faisal, Ghasak Ghazi; Mohammad, Ahmad (2020)
Intrauterine insemination is amongst the foremost recommended procedures to reinforce the probability of pregnancy in couples with infertility. The success rate of this system depends on numerous factors, one among which is that the quality of the luteal phase which could be due to insufficient production of progesterone. To study the impact of luteal phase GnRH agonist versus HCG supplementation on pregnancy rates in females undergoing intrauterine insemination. This study was performed on random 40 infertile couples. Basal hormones measurement of FSH, LH, E2 and progesterone was done before undergoing ovarian stimulation by letrozole or clomiphene citrate. In the mid cycle transvaginal ultrasound was done to measure the dominate follicle/ s and endometrial thickness (ET). Assessment of progesterone and E2 was done on the trigger day. Triggering of ovulation was done by the HCG injection (5000IU). IUI for all females included in the study then they were divided into two groups of 20. Group A were supplemented with GnRH agonist injections (0.1 mg) on day 9,10,11,12 post IUI plus progesterone suppositories 400 mg for 14 days while group B were supplemented with HCG injections 1500IU on day 1, 4, 7 post IUI plus progesterone suppositories 400 mg for 14 days. Then Progesterone level was re measured at day 21 of the cycle. Chemical pregnancy rate was done and recorded. The hormonal levels showed no significant difference in baseline serum FSH, LH and estradiol (E2) (P > 0.05); however, there was significant difference in mean serum baseline progesterone between protocol groups (p= 0.024); additionally, there was no significant difference in mean serum estradiol (E2) and progesterone at day 12 (p> 0.05), but the difference in mean serum progesterone at day 21 was highly significant (p < 0.001); its level was highest in group B than A. The pregnancy rate of infertile women in groupA (who used GnRH as supportive to luteal phase) was higher (40.0 %).Conclusions: Luteal phase support by GnRH injection (Decapeptyl 0.1mg) significantly increased pregnancy rate in infertile females undergoing intrauterine insemination compared to HCG injection (1500IU) in spite of significant elevation in progesterone hormone at 21the day in HCG group.